Conflict: a cause and effect of hunger - Messer, Ellen; Cohen, Marc J.; Marchione, Thomas (2001)
If the slogan of the 1996 World Food Summit »Food for All« is to become a reality, then cycles of hunger and conflict must be broken, especially in Africa. Whether one accepts the view that environmental scarcities, including food insecurity, cause conflict, or believes that conflict is primarily caused by political factors, access to food is always disrupted by conflict. We review here what is known about the linkages between hunger and conflict, and suggest what can be done to break these connections.